DENSITY OF Escherichia coli BACTERIA IN MUDSKIPPER (Periophtalmus schlosseri) IN DUMAI CITY RIAU PROVINCE - Abdul Hafiz; Feliatra Feliatra; Nursyiwani Nursyiwani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT Escherichia coli in marine ecosystems have an important role as aquatic bioindicators. The E. coli group can be found in various habitats including the skin and digestive organs of the Mudskipper fish. This research was conducted from September - November 2018 in Purnama Urban Village, Dumai City, Riau Province. The research method used is the survey method and the method of determining the sampling location is purposive. The measured water quality factors are Temperature, Salinity and pH and the calculated indicator is the density of E. coli bacteria, bacterial analysis using MPN method series 3 tube. The number of E. coli bacteria on the skin of the Mudskipper fish ranged from 2.1 x 104- 1.1 x 105with the highest average found at station 1 and the lowest at station 2. While the number of E. coli bacteria in the digestive organs of the Mudskipper fish ranged from 2 x 103-1.1 x 105with the highest average was at station 1 and the lowest at station 3. 24 E. coli bacterial isolates were selected for the Biochemical test where 24 isolates of E. coli were Gram negative and Catalase positive. 19 isolates were motile and 5 isolates were inmotile, 11 isolates positive produced indole and 13 isolates negative indole, 16 isolates were able to produced H2S, 8 isolates were unable to reduce H2S. 24 isolates could ferment glucose, lactose and cellulose, 3 isolates were positive methyl red and 21 isolates were negative methyl red. 20 E. coli bacterial isolates were able to ferment citrate and 4 isolates were unable to ferment citrate. Keyword : Density, Esterichia coli, Mudskipper Fish